Creación de la Unidad de Vinculación con la Colectividad en la Universidad Andina Simón Bolívar, Sede Ecuador. - Mantilla Aslalema, Zamira Zenayda (2014)
The Universidad Andina Simón Bolívar (UASB)3, Sede Ecuador, serves two specific purposes, one directed toward graduate programs Superior Specialization, Masters and PhD and the other to meet bonding activities with the community (AC)4. This research work emphasizes the importance of these activities, such as, courses, academic activities and academic events and how they can be developed in compliance with quality standards and continuous monitoring of national organizations. There are currently many flaws in the development of these activities, the UASB has grown considerably but it still maintains inadequate procedures. This thesis discusses in detail the benefits and the imperative need for the creation of a unit that runs and support the good fulfillment of the University, being responsible for enforcing processes and administrative policies for the execution of all activities related to bonding with the community in all areas, departments and other unities of the University. This unit will operate totally independently, with a suitably designed information system that will record the entire process from beginning to finish, thus assuring optimum results and complying with the standards of a university of excellence.